2022
DOI: 10.1021/acs.energyfuels.1c03967
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Effect of Organic Matter on Accumulation Behaviors of Shale Gas in Water

Abstract: Hydraulic fracturing technology is widely used in unconventional oil and gas exploitation. The existence of water makes the interactions between oil and gas and the interface more complex. Therefore, it is important to understand the interaction between gas and solid in a water environment. In the paper, we construct a generalized charged plate to study the accumulation and diffusion of shale gas on the solid interface in a water environment. The atomic arrangement of the charged interface has an essential inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The peak with the highest water density appears at a distance of 0.335 from the interface. It has been reported that the water molecules near the interface are ordered, allowing the interface to hold more water molecules than the bulk region . When an electric field is applied, there is a significant increase in the peak density of the water molecules, which means that the water molecules prefer to approach the interface under the action of the electric field.…”
Section: Resultsmentioning
confidence: 99%
“…The peak with the highest water density appears at a distance of 0.335 from the interface. It has been reported that the water molecules near the interface are ordered, allowing the interface to hold more water molecules than the bulk region . When an electric field is applied, there is a significant increase in the peak density of the water molecules, which means that the water molecules prefer to approach the interface under the action of the electric field.…”
Section: Resultsmentioning
confidence: 99%
“…Competitive adsorption between CO 2 and CH 4 during carbon dioxide flooding refers to the preferential adsorption of either species by the adsorbent when the two gas components coexist in the reservoir . In shale gas reservoirs, CO 2 –CH 4 competitive adsorption is affected by various factors related to CO 2 injection conditions, geological conditions, and shale matrix compositions. , Such factors may include the total organic carbon content (TOC), kerogen type, inorganic minerals, pore structure, thermal maturity, CO 2 -shale affinity, the molecular structure of the gas, and oxygen-containing functional groups . Hydraulic fracturing leads to shale gas pore-scale transport to a multiphase and multiphysical process.…”
Section: Multiscale Flow Simulationmentioning
confidence: 99%